Community Dedication on General Facilities Using Solar Cell System in Kalialo Village, Kupang, Jabon, Sidoarjo - Boy Isma Putra; Jamaaluddin Jamaaluddin; Shazana Dhiya Ayuni (Kontribusia : Research Dissemination for Community Development, 2021)
In essence, road access to Kalialo Village is still very difficult due to the dark terrain and street lighting (PJU), this is because the PJU electricity in the village has been cut off since the last 6 months. Kalialo Village has provided information to PLN regarding the cut off of public street lighting but has not received any response to date.To help and facilitate this access, we as the Center for Engineering and Energy Studies feel the need for a Solar Power Plant (PLTS) or Solar Cel. Which will be installed at certain vital points or locations on the road access to Kalialo Village.